‘No sex under my roof’: Teenage sexuality in the USA and in the Netherlands since the 1880s - Wouters, Cas (Política y Sociedad, 2013)
The oneliner ‘No sex under my roof’ is used to reinforce the rule of premarital abstinence of sexuality until teenage children marry or move from home. In the USA, most parents still stick to this norm, whereas in the Netherlands since the late 1960s, a new rule developed, allowing teenage children to have sex, provided they ‘feel strongly for each other’ and feel ‘ready’ for it. This paper describes and compares developments in the USA and in the Netherlands since the 1880s, focusing on the social regulation of teenage sexuality, and based mainly upon such sources as reference books and sexology studies. The paper proposes an explanation of the two trajectories from national differences in the functioning of good societies, particularly in the regulation of social competition and social mobility. The rise in the USA of a highly competitive dating system and a complicated sexual morality indicates a smaller decline of power differences between classes, genders and generations, which partly explains the persistence of the old rule. Further explanation is found in America’s lower level of social integration and more open competition between various centres of power and good societies. The build up to the rise of a new rule among Dutch parents was an informalization of ‘getting engaged’, the diffusion of verkering (going steady) and of parental policies to stay ‘in the scene’, indicating higher levels of social integration and larger declines of power differences between classes, genders and generations. Yet, the long preservation of a homogeneous good society created a widening gap between a facade of decency and backstage realities. When this gap was washed away in the 1960s Expressive and Sexual Revolutions, it also washed away the old rule, and increasing numbers of parents allowed their teenagers openly to have sex, even at home.